Three centuries of technological innovation: Opportunity is the mother of invention - Jordan G. Okie; James H. Brown; Astrid Kodric-Brown; Joseph R. Burger; Tatiana P. Flanagan; Trevor S. Fristoe; Sean T. Hammond; Norman Mercado-Silva; Jeffrey C. Nekola; Jennifer Richter (Proceedings of the National Academy of Sciences, 2026)
What socioecological conditions nurture the ingenuity and collaborative interactions underlying transformative technological innovations? We compiled a dataset on more than 400 major technological inventions from 1690 to 1990 spanning seven categories (agriculture, armaments, information and communication, household, industry, medical, and transportation) and performed inductive macroecological analyses to address how attributes of inventors, teams, and their social and geographic environments contributed to the innovation of new technologies that have changed the way people live. The vast majority of inventions were attributed to single inventors of various ages. The frequency, size, and cultural diversity of teams increased in the 20th Century, as did the proportion of inventions attributed to women and immigrants. A wide variety of environments acted as innovation hubs, including rural areas as well as specialized institutions and large cities. Invention rate (number of inventions per time period) peaked during the 1800s in cities, rural areas, and most categories but continued increasing over time in institutional environments and medical and communication technologies. The overall pattern across ages, genders, team attributes, environments, technological categories, and time periods supports the conclusion that opportunity, ingenuity, and environment all play key roles in the inventiveness phase of the innovation process: creative individuals in particular ecological environments and social settings come up with novel solutions to specific practical problems. Similar innovation patterns have been observed for tool use among nonhuman primates, highlighting unifying processes of innovation. Our macroecological approach offers valuable insights into the emergence and drivers of innovation and material culture.